INTERVAL CALIBRATION MODEL OF MULTISENSOR SYSTEM - Voschinin, Alexander; Skibitski, Nikita (International Journal of Computing, 2014)
Problem of multisensor system calibration is of great importance in a number of applications. Most often the problem is solving by means of statistical methods using data of calibration controlled experiment. However, in many cases uncertainty and inaccuracy of experimental data more reasonably to express not in terms of random errors but in terms of known bounded absolute errors. For this case based on the introduced definition of “interval readings” interval calibration model is suggested. Within interval paradigm all calibration subproblems are reasonably solved including sensor sensitivity test, most accurate sensors subset selection and aggregate estimation of measurable variable uncertainty interval. There are given a numerical examples.